2019
DOI: 10.5114/wiitm.2019.88751
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted excision of thyroglossal duct cyst by a postauricular facelift approach.

Abstract: AimHerein, we describe the surgical procedure used and the early surgical outcomes of this novel technique based on our experience of six cases. A b s t r a c tIntroduction: A trend towards robotic scarless surgery using remote site incisions has developed in head and neck surgery for better cosmetic outcomes. We have carried out robot-assisted excision of thyroglossal duct cysts (TGDC) by a postauricular facelift approach to avoid visible scars in the central neck related to the trans-cervical Sistrunk operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Many have reported experience with the transoral endoscopic thyroidectomy vestibular approach (TOETVA), which has been demonstrated to have similar outcomes to the traditional transcervical thyroidectomy 4 . Approaches have similarly been identified to excise TGDCs without leaving an external neck scar, including techniques via transaxillary 7 and postauricular 8 incisions. In 2011, Kim et al reported a transoral Sistrunk procedure using a frenotomy incision without insufflation.…”
Section: Discussionmentioning
confidence: 99%
“…Many have reported experience with the transoral endoscopic thyroidectomy vestibular approach (TOETVA), which has been demonstrated to have similar outcomes to the traditional transcervical thyroidectomy 4 . Approaches have similarly been identified to excise TGDCs without leaving an external neck scar, including techniques via transaxillary 7 and postauricular 8 incisions. In 2011, Kim et al reported a transoral Sistrunk procedure using a frenotomy incision without insufflation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent approaches to TDC surgery such as robot-assisted or endoscope-assisted transoral, retroauricular, and axillary approaches have been described for adult patients. [ 13 14 15 16 ] These approaches promise better cosmesis by avoiding anterior neck incision, but their efficacy compared to the traditional Sistrunk procedure remains a subject of further research.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the advancement of remote access head and neck surgery, there has been a growing interest in exploring robotic-assisted Sistrunk operations using various external cervical approaches. The commonly utilized external cervical approaches for robot-assisted TGDC resection include the transoral approach ( 22 , 23 ), transoral approach using vestibular and sublingual incisions ( 24 ) and postauricular facelift approach ( 25 ). While all these approaches have been proven to be safe and feasible with excellent postoperative cosmesis, they each come with certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%